An assessment of the invasion state and fisheries suitability in four dams and a natural lake in the Western Cape, South Africa - Dredge, Brendon Neville (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2016)
Despite more than a century of introductions, fish invasions are poorly understood in South Africa. This thesis aims to: (1) provide baseline information on the fish fauna in five inland water bodies (four dams: Theewaterskloof, Clanwilliam, Quaggaskloof, and Voelvlei and a natural lake, Groenvlei) in the Western Cape; (2) determine which species were established and provide a baseline of abundance and size structure for monitoring and, (3) make preliminary recommendations for a fishery. First, criteria for determining establishment were developed by undertaking a full biological assessment of bluegill Lepomis macrochirus, a data-poor species in South Africa. This included the assessment of growth rate using validated estimates of age derived from otoliths in two dams (Clanwilliam Dam: Lt=335.9(1−eo.113(t+1.06)); Groenvlei: Lt=287.2(1-e−0.171(t+0.54)). Length at 50% maturity was similar for males (146 mmFL) and females (147 mmFL). Length frequency analysis combined with data on the age and growth and reproduction demonstrated that established populations of bluegill contained several age cohorts as well as mature and juvenile fishes. A meta-analysis was conducted to: (1) compile a list of initial stocking dates for all alien fishes in each waterbody and (2) use angler tournament data to assess for additional species and persistence over time. Data from the meta-analysis was combined with ichthyological survey data to determine establishment success. These data demonstrated that nine non-native species had established in the five water bodies. Clanwilliam Dam had the largest number (7) of non-native species established, Groenvlei (5) and Theewaterskloof, Brandvlei and Voelvlei the lowest with four species. The state of invasion of each species in the province showed that all nine species are categorised as invasive. This information on establishment was then integrated into a framework for rapidly determining what type of fishery would be most suitable for the 5 waterbodies. Potential yield was estimated using morphoedaphic models, were 260 t/yr for Theewaterskloof Dam, 93 t/yr for Voelvlei, 81 t/yr for Brandvlei, 59 t/yr for Groenvlei and 55 t/yr for Groenvlei. The CPUE for Groenvlei was the highest in gill nets with 1.32 ± 1.94 kg/h, then Voelvlei 1.05 ± 1.34 kg/h followed by Brandvlei (0.84 ± 1.48 kg/h), Clanwilliam (0.71 ± 1.55 kg/h) and lastly Theewaterskloof (0.36 ± 0.41 kg/h). Only Theewaterskloof could produce in excess of 100 t/yr but less than 400 t/yr of fish making it suitable for a small scale fishery. The CPUE values of Theewaterskloof were the lowest and a gill net fishery on this water body may not produce sufficient fish for the fishery. All water bodies had a high recreational angling usage, the opening of a small scale fishery could be detrimental to this industry. Subsistence and recreational anglers should be promoted with the possibility of a long line industry targeting Clarias gariepinus.
Keywords: Introduced organisms; Fishery management -- South Africa -- Western Cape; Fishes -- Conservation -- South Africa -- Western Cape; Introduced fishes -- South Africa -- Western Cape